Understanding Benign Liquidity Traps: The Case of Japan - Stefan Homburg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Japan has been in a benign liquidity trap since the 1990s. In a benign liquidity trap, interest rates approach zero and monetary policy is ineffective but output and employment perform decently. Such a pattern contradicts traditional macro theories. This paper introduces a monetary general equilibrium model that is compatible with Japan's performance and resolves puzzles associated with liquidity traps. Possible conclusions for Anglo-Saxon countries and eurozone members are also discussed
Keywords: E31; E43; E52; 330